Students’ Perceptions towards Ideal Maritime English Teacher - Laila Puspitasari Anggraini; Ernis Ernis; Joanna Maria Jelenska (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2020)
This paper discusses the perceptions of students about the characteristics of an Ideal Maritime English teachers in a vocational institution. It is an interpersonal point of view regarding of their perceptions of qualities of English teachers and teachers’ immediacy behavior (verbal or non-verbal) as a students’ academic motivation. A total of 60 students of 3 departments of the 2nd level was randomly involved. Results of this study show that students and teachers described the ideal teacher as a person who is friendly, young, enthusiastic, creative and humorous person whose gender is not important. Also, students expect their teacher to be a native speaker of Indonesian but fluent in English, someone who like to play educational games, and who teaches maritime context effectively by using real life situations to explain language item. The aim of this study is expected to give understanding of how teaching Maritime English in a foreign language context can be better.